Corporate Sustainable Performance in Indonesia: Insights, Gaps, and Research Directions - Nouke Sysca Oroh (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to map and synthesize the research landscape of corporate sustainable performance in Indonesia by identifying dominant themes, theories, methods, and future research directions. Research Method: The study employs a systematic bibliometric approach to analyze prior studies on corporate sustainable performance in Indonesia. The analysis, using the TCCM framework, focuses on research themes, theoretical foundations, methodological choices, authorship patterns, institutional contributions, and research gaps. Results and Discussion: The findings reveal a strong dominance of quantitative methods, especially survey-based designs and SEM/PLS-SEM analysis. The literature relies heavily on stakeholder theory and the resource-based view. Key research themes include sustainability, corporate social responsibility, corporate governance, and financial performance, while emerging topics include environmental innovation, ESG, and organizational capabilities. The field shows a semi-concentrated authorship and institutional structure, indicating established scholarly leadership and growing participation. Implications: The study suggests the need for greater theoretical diversity, deeper contextual analysis, and more robust methodologies, including longitudinal and theory-driven approaches. The findings also provide insights for firms and policymakers to integrate sustainability into corporate strategy and governance. Originality: This study provides a structured overview of research on corporate sustainable performance in Indonesia and identifies key research gaps using the TCCM framework.